Didactic Factors of Improving the Writing Competence of Future English Language Teachers - Sotvoldievich, Toshmatov Alimardon (Journal of Higher Education and Academic Advancement, 2024)
This study aims to investigate the didactic factors and strategies that contribute to improving the writing competence of future English language teachers. Using a mixed-methods approach, the study surveyed and interviewed pre-service teachers and analyzed their written work. The results revealed that targeted feedback, practice-oriented instruction, collaborative learning, and self-regulated learning were significant contributors to enhancing writing competence. These findings have implications for teacher education programs and the professional development of future English language teachers.